Strategies to Control Loropetalum Decline in Central Florida - Amy L. Shober; Gary L. Leibee (EDIS)
SL-255, a 5-page illustrated fact sheet by Amy L. Shober and Gary L. Leibee, describes this unexplained condition affecting the Ruby cultivar of this popular woody ornamental plant (also called Chinese fringebush or Chinese witch hazel) in central Florida. It presents the results of two studies conducted to identify possible causes and develop management methods. It includes suggested alternative cultivars and treatment recommendations for existing plantings. Published by the UF Department of Soil and Water Sciences, October 2007.